2015
DOI: 10.1017/s1092852915000012
|View full text |Cite
|
Sign up to set email alerts
|

Advances from neuroimaging studies in eating disorders

Abstract: Over the past decade brain imaging has helped better define eating disorder related brain circuitry. Brain research on gray and white matter volumes had been inconsistent, possibly due to the effects of acute starvation, exercise, medication and comorbidity, but newer studies controlled for such effects. Those studies suggest larger left medial orbitofrontal gyrus rectus volume in ill adult and adolescent anorexia nervosa after recovery from anorexia nervosa, and in adult bulimia nervosa. The orbitofrontal cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
0
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(101 citation statements)
references
References 104 publications
(142 reference statements)
6
80
0
12
Order By: Relevance
“…Our findings are also consistent with insular anatomical abnormalities documented in both ill adult and adolescent AN and remitted adults (Frank 2015; Shott et al 2015). …”
Section: Discussionsupporting
confidence: 90%
“…Our findings are also consistent with insular anatomical abnormalities documented in both ill adult and adolescent AN and remitted adults (Frank 2015; Shott et al 2015). …”
Section: Discussionsupporting
confidence: 90%
“…Several studies, investigating these networks, corroborate the existence of changes in sensorimotor and visual networks in ED patients either in terms of functional connectivity [15,21], which looks at correlations between brain regions [22], or in effective connectivity [23], which establishes causal effects between neural systems.…”
Section: Connectivity Studies In Edmentioning
confidence: 85%
“…Furthermore, functional magnetic resonance imaging (fMRI) is also frequently used, by measuring changes in local blood flow and deoxyhemoglobin levels during brain activation. Other techniques like positron emission tomography (PET) and single photon emission computed tomography (SPECT) are also used, providing information about regional cerebral glucose metabolism or the distribution of neurotransmitter receptors [15].…”
Section: Neuroimaging Studies In Edmentioning
confidence: 99%
“…Those studies usually do not test brain neurotransmitters directly, but the response during tasks that test specific behaviors might help in understanding neurotransmitters involved in the brain response [108]. In such studies during fMRI, individuals with AN showed greater brain activation compared to controls when viewing anxiety-provoking food pictures; during taste or monetary reward tasks, individuals with AN tended to show increased activation to unexpected stimulus presentation, while brain response tended to be lower when the specific stimulus was expected [109]. Importantly, a paradigm that specifically targets dopamine-related pathways (prediction error model [110]) suggested increased brain responsiveness in AN, implying high dopamine receptor sensitivity, which is consistent with basic science research.…”
Section: Neurobiology Of Anmentioning
confidence: 99%